2020
DOI: 10.1111/liv.14445
|View full text |Cite
|
Sign up to set email alerts
|

Non‐amyloid liver involvement in familial Mediterranean fever: A systematic literature review

Abstract: Introduction: Familial Mediterranean fever (FMF), the most frequent autoinflammatory disease, is caused by mutations in the MEFV gene. It is characterized by recurrent febrile attacks of polyserositis. Liver abnormalities may develop during its course, but they remain poorly defined.Objective: To describe liver involvement in FMF patients. Methods:A systematic search was conducted through PubMed/Medline and Embase from 1946 to January 2020. All articles describing children and adults with FMF and liver involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 72 publications
0
11
0
Order By: Relevance
“… 1 , 5 – 7 , 10 , 27 , 28 For a long time, the liver was not considered typically involved in FMF, and AA amyloidosis was considered the only possible culprit in the case of hepatic involvement. 12 However, an increase of liver enzymes does not occur in the case of amyloidosis, 13 as the most frequent signs of liver AA amyloidosis are an increased level of alkaline phosphatase and hepatomegaly. 29 …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“… 1 , 5 – 7 , 10 , 27 , 28 For a long time, the liver was not considered typically involved in FMF, and AA amyloidosis was considered the only possible culprit in the case of hepatic involvement. 12 However, an increase of liver enzymes does not occur in the case of amyloidosis, 13 as the most frequent signs of liver AA amyloidosis are an increased level of alkaline phosphatase and hepatomegaly. 29 …”
Section: Discussionmentioning
confidence: 99%
“… 30 , 31 Experiments in mice have shown that an abundant release of IL-1 causes inflammation, pyroptosis, and collagen deposition in the liver with subsequent increase of liver enzymes. 13 , 32 Two conflicting studies have enhanced our knowledge about the connection between FMF and liver involvement, and more between FMF and nonalcoholic fatty liver disease (NAFLD). The survey conducted by Rimar et al enrolled 27 patients with FMF but without a frank metabolic syndrome and found that 75% of patients had NAFLD.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations